Bonding With Parents, Body Image, and Sociocultural Attitudes Toward Appearance as Predictors of Eating Disorders Among Young Girls - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Wajda, Zbigniew; Lizińczyk, Sebastian; Ściegienny, Aleksandra (Frontiers in Psychiatry, 2021)
A more holistic approach to treatment and prevention focuses on identifying the multiple risk and protective factors for eating disorders. However, there is a lack of research verifying the nature of the relationship between the patterns of bonding with parents, the sociocultural attitudes towards appearance, the body image, and their role in developing or preventing eating disorders. The main aim of the study was to verify whether, there is a specific set of risk or/vs protective ones/measures for behaviors and dispositions related to the development of eating disorders. The study group comprised 134 polish young females (M=14.92; SD=1.349), with average BMI. The variables were measured using the Parental Bonding Instrument PBI, Sociocultural Attitudes Towards Appearance Scale SATAQ-3, The Multidimensional Body-Self Relations Questionnaire MBSRQ-AS, and Eating Disorders Inventory EDI 3. The stepwise regression analysis was applied. The statistical analysis showed that the bonding with parents (including maternal overprotection), body image (including overweight preoccupation, fitness evaluation, health orientation, self classified weight) and socio-cultural attitudes towards appearance (such as searching for information, pressures, and internalization) are predictors of eating disorder risks. On the other hand, the maternal and paternal care (aspects of patterns of bonding with patents), positive fitness evaluation, positive appearance evaluation, and satisfaction of one’s body were found to be the most significant protective factors. The results may improve the prevention and intervention aimed to increase protective factors.